Policy and Institutional Dynamics of Sustained Development in Botswana - Maipose, Gervase S. (World Bank, Washington, DC, 2017)
Botswana represents one of the few development success stories in Sub-Saharan Africa. Real Gross Domestic Product (GDP) growth averaged almost 9 percent between 1960 and 2005, far above the Sub-Saharan Africa average. Real GDP per capita grew even faster, averaging more than 10 percent a year -- the most rapid economic growth of any country in the world. The crucial question is: Why has Botswana grown the way it has done, and what lessons does it offer? This evidence-based story is an account of policy and institutional dynamics of sustained growth and development in Botswana -- illuminating the role of leadership. It shows how a secure political elite has pursued growth-promoting policies and developed, modified, and maintained viable inherited traditional and modern institutions of political, economic, and legal restraint. These institutions have remained robust in the face of initial large aid inflows and spectacular mineral rents, producing a growth pattern that has been both rapid and cautious. The nature of the Botswana developmental state is illustrated by the way in which the state mobilized development resources-especially savings, investment, and human resources, widely known as the primary drivers of economic growth, and prudently managed the economy without becoming excessively involved in the nuts. It demonstrates that through intentional policy choices and countercyclical instruments, countries can shift from aid-dependent to trade-led natural resource development (though probably with narrow-based growth), to a broader development strategy as long as the state is capable and operates within effective institutional design. Botswana's story is sterling example of how the critical issue in development is not so much access to resources but how resources are managed.